Răspuns :
⇒
a-2 | a²-3a+4
a-2 | a - 2 l · (a-2)
______________________ ⇔
a-2 | a² -3a +4
a-2 | (a-2)² | · (-1)
________________⇔
a-2 | a²-3a +4
a-2 | -(a²-4a+4)
________________⇔
a-2 | a²-3a + 4
a-2 | -a² +4a -4
_____________+ le adunam
a-2 | aa-2 | a si mai stim ca a-2 l a-2
deci
a-2 | a l ·(-1)
a-2 | a-2
_____________⇔
a-2 | -a
a-2 | a-2
_____________+
a-2 | -2 ⇒ a-2 ∈ D₋₂ ={2,-2,1,-1}
Si luam pe cazuri
CAZ I ↓
a-2 = 2 ⇒ a = 4 ∈ Z
CAZ II ↓
a-2 = -2 ⇒ a = 0 ∈ Z
CAZ III ↓
a-2 = 1 ⇒ a = 3 ∈ Z
CAZ IV ↓
a-2 = -1 ⇒ a = 1 ∈ Z
deci a ∈ {4,0,3,1}
[tex] \it \dfrac{a^2-3a+4}{a-2} = \dfrac{a^2-2a-a+2+2}{a-2} = \dfrac{a(a-2)}{a-2} - \dfrac{a-2}{a-2} + \dfrac{2}{a-2}=
\\ \\ \\
= a-1+ \dfrac{2}{a-2} \in \mathbb{Z} \Rightarrow a-2|2 \Rightarrow a-2\in D_2 \Rightarrow a-2 \in\{\pm1,\ \pm2\}\Rightarrow
\\ \\ \\
\Rightarrow a-2\in \{-2,\ -1,\ 1,\ 2\}|_{+2} \Rightarrow a\in\{0,\ 1,\ 3,\ 4\} [/tex]